Downtime cost analysis of offloading operations under irregular waves in Malaysian waters - Patel, M.S.; Liew, M.S.; Mustaffa, Z.; Abdurasheed, A.S.; Whyte, Andrew (Techno Press, 2020)
© 2020 Techno-Press, Ltd.